Experiences and Satisfaction of Scuba Dive Tourists in Cambodia: A Case Study of Sihanoukville - Kunthea, Phirum (Auckland University of Technology, 2016)
Sihanoukville is Cambodia‟s most popular coastal and marine tourism destination and scuba diving tourism has been gradually increasing. Although the tourism sector has been increasing, research has paid very little attention to this phenomenon. This study is the first empirical research focusing on the experiences and levels of satisfaction of scuba dive tourists in Sihanoukville. Mixed methods, using both quantitative and qualitative techniques, were employed in this study by distributing self-reply questionnaires and conducting semi-structured interviews. The results reveal a profile of scuba divers who predominantly came from Western countries with relatively high incomes, ranging from young to middle age groups and mostly travelling alone. There were more males than females. Most scuba divers to Sihanoukville were motivated to see life under the sea and several attributes contributed to their satisfactory experience: taking photos underwater, socialisation, watching marine life and seeing rare things which they had never seen before. However, results show other factors that can lead to negative diving experiences such as overfishing, dynamite fishing, and waste disposal. The findings also indicated that scuba divers wish to see future changes such as artificial reefs and wrecks and the outlawing of illegal fishing. This first study on scuba diving in Cambodia offers recommendations for key stakeholders to take into account so that the dive experience can be improved and scuba diving tourism sustained in Sihanoukville. Other implications are also proposed for future research.
Keywords: Scuba diving tourism; Experience; Satisfaction; Sihanoukville; Cambodia